A qualitative study on experiences of mothers about control of diarrhoea of their children - Barik, Kanai Lal; Paul, Uttam Kumar (International Journal of Contemporary Pediatrics, 2019)
Background: Diarrheal disease poses a significant problem to the health, wellbeing and survival of children of less than five-year age group and is the second leading cause of mortality. Most of the deaths are due to dehydration and it can be preventable by proper and timely use of oral rehydration salt solution (ORS). There is lack of awareness among the mothers about the appropriate use of ORS during diarrhea of children. So, authors have tried to find out the experiences of the mothers about the management of diarrhea of their children. Methods: The study is one of qualitative descriptive type involving 27 mothers of children who are suffering from diarrhoea in face to face in depth interviews (IDI). Results: The mothers of children were within the age group of 21 to 34 years of age group. On the basis of qualitative data analysis, the present study shows the data related to childhood diarrhea can be classified under six themes. The themes are : ’Perception of the participant mothers about the diarrhea of their babies’, ’Measures taken by the mothers to combat diarrhea at home’, ’How Oral rehydration salt solution is applied by the mothers’, ’How Oral rehydration salt solution is beneficial’, ’How Oral rehydration salt solution is causing undesirable effects on the baby’ and ’What additional measures taken to control diarrhea of the baby’. Conclusions: There are several misconceptions and lack of awareness of the mothers about management of diarrhoea. However, it is possible to create awareness among them so that they can take all suitable measures to control diarrhoea.